Grlom u jagode (Episoda 9) - Glava ili pismo - Karanović, Srđan (Yugoslavia : RTV Beograd, 1975)
As Bane and his friends get older – money begins to play a major role in their lives and the first differences in their standards of living appear as not all of them are equally successful. Approaching the end of his studies and wishing to earn his own living Bane starts working as a steward on a plane and helps his budget by smuggling imported cigarettes and alcohol. He continues his relation with Svetlana, but again gets involved with his former girlfriend Goca who eventually turns out to be pregnant. Although Bane is the real father, Goca decides to marry Bane’s ex-best friend Uške. The episode ends with the two of them slapping each other, knowing that their friendship will never be the same again.
Keywords: Yugoslavia